Somatic mutations and promotor methylation of the ryanodine receptor 2 is a common event in the pathogenesis of head and neck cancer. Issue 12 (19th June 2019) - Schmitt, Katrin; Molfenter, Britta; Laureano, Natalia Koerich; Tawk, Bouchra; Bieg, Matthias; Hostench, Xavier Pastor; Weichenhan, Dieter; Ullrich, Nina D.; Shang, Viny; Richter, Daniela; Stögbauer, Fabian; Schroeder, Lea; et al.
Abstract : Genomic sequencing projects unraveled the mutational landscape of head and neck squamous cell carcinoma (HNSCC) and provided a comprehensive catalog of somatic mutations. However, the limited number of significant cancer‐related genes obtained so far only partially explains the biological complexity of HNSCC and hampers the development of novel diagnostic biomarkers and therapeutic targets. We pursued a multiscale omics approach based on whole‐exome sequencing, global DNA methylation and gene expression profiling data derived from tumor samples of the HIPO‐HNC cohort ( n = 87), and confirmed new findings with datasets from The Cancer Genome Atlas (TCGA). Promoter methylation was confirmed by MassARRAY analysis and protein expression was assessed by immunohistochemistry and immunofluorescence staining. We discovered a set of cancer‐related genes with frequent somatic mutations and high frequency of promoter methylation. This included the ryanodine receptor 2 (RYR2), which showed variable promoter methylation and expression in both tumor samples and cell lines. Immunohistochemical staining of tissue sections unraveled a gradual loss of RYR2 expression from normal mucosa via dysplastic lesion to invasive cancer and indicated that reduced RYR2 expression in adjacent tissue and precancerous lesions might serve as risk factor for unfavorable prognosis and upcoming malignant conversion. In summary, our data indicate that impaired RYR2 function by either somatic mutation or epigenetic silencing is a common event in HNSCC pathogenesis. Detection of RYR2 expression and/or promoter methylation might enable risk assessment for malignant conversion of dysplastic lesions. Abstract : What's new? Multi‐scale omics approaches provide a powerful tool to unravel cancer‐related genes with the potential to serve as prognostic biomarkers and putative drug targets. This study shows that somatic mutations and epigenetic silencing of the ryanodine receptor 2 (RYR2) are frequent in head and neck cancer. Loss of RYR2 expression was found during transition from dysplastic lesions to invasive tumors. Detection of somatic mutations or promoter methylation might thus improve risk assessment of malignant conversion, which could enable timely and adequate treatment of premalignant lesions.